Effects of yttrium addition on microstructure and mechanical property of Nb-1Zr-0.1C alloy - Wanxin Liu; Shengjie Wang; Xiaoxin Zhang; Yanchang Liu; Bin Liang; Shilei Li (Materials Letters: X)
The effects of Y addition on microstructure and mechanical property of Nb-1Zr-0.1C alloy were investigated. Electron backscattered diffraction results show that no recrystallization was observed in the warm-rolled and annealed Nb-1Zr-0.1C alloys with different Y additions. In the cold-rolled and annealed Nb-1Zr-0.1C alloy with 0.1 % Y addition, Y2O3 was continuously distributed along the grain boundaries of the Nb matrix that had undergone complete recrystallization. While as the Y addition increased to 0.4 %, Y2O3 restored a granular distribution in the cold-rolled and annealed Nb-1Zr-0.1C alloy. The addition of Y element to the Nb-1Zr-0.1C alloy could enhance both the strength and plasticity to a certain extent. Compared with the as-cast and warm-rolled and annealed samples, the Nb-1Zr-0.1C alloy with different Y additions after cold-rolling and annealing exhibited a higher work hardening rate.